Source of apportionment of air quality parameters at federal port of Malaysia with emphasis on ship emission - Azman, Azid; Samsudin, M.S.; Razik, M.A.; Zaudi, M.A.; Shaharudin, S.M. (2021)
Air pollution is becoming a major environmental issue in Malaysia. Centered on data obtained from the Malaysian Department of Environment (DOE), this analysis focused on identifying possible causes of air quality heterogeneity across the research area. 14 air quality parameters in 7 monitoring stations for ten years (2009-2018) were gathered. To determine the source of air pollution around the study region, the Principal Component Analysis (PCA) approach from a chemometric methodology was applied. The PCA method has identified three varimax factor (VF) with 11 air quality parameters are the most significant parameters around the study area. It can be inferred from the analysis that the use of the PCA approach in chemometric techniques can be applied for the purpose of source apportionment. Accordingly, this study suggested that efforts should be put as a priority in the monitoring of ships emissions sources in Malaysia Federal Ports area and successful management of Malaysian air quality.